The Contemporary Reader of Gender and Fat Studies - Farrell, Amy (Taylor & Francis, 2023)
The Contemporary Reader of Gender and Fat Studies is a key reference work in contemporary scholarship situated at the intersection between Gender and Fat Studies, charting the connections and tensions between these two fields. Comprising over 20 chapters from a range of diverse and international contributors, the Reader is structured around the following key themes: theorizing gender and fat; narrating gender and fat; historicizing gender and fat; institutions and public policy; health and medicine; popular culture and media; and resistance. It is an intersectional collection, highlighting the ways that ""gender"" and ""fat"" always exist in connection with multiple other structures, forms of oppression, and identities, including race, ethnicity, sexualities, age, nationalities, disabilities, religion, and class. The Contemporary Reader of Gender and Fat Studies is essential reading for scholars and advanced students in Gender Studies, Sexuality Studies, Sociology, Body Studies, Cultural Studies, Psychology, and Health. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons [Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND)] 4.0 license.